Enhanced electrochemical oxidation of phenol over manganese oxides under mild wet air oxidation conditions. (20th May 2018) - Massa, Andrea; Hernández, Simelys; Ansaloni, Simone; Castellino, Micaela; Russo, Nunzio; Fino, Debora
Abstract: Low-cost manganese oxide, MnOx-based electrocatalysts, containing α-MnO2 and mixed α-Mn2 O3 /α-MnO2 phases, were synthesized by scalable anodic and cathodic electrodeposition methods, respectively. Their morphological and chemical composition were characterized by means of Field Emission Scanning Electronic Microscopy (FESEM), X-Ray Diffraction (XRD) and X-ray Photoelectron Spectroscopy (XPS). These electrodes were tested for the electro-oxidation of a recalcitrant molecule ( i.e. phenol) in a lab-scale high temperature and high pressure (HTHP) batch electrocatalytic reactor. Their electrocatalytic activity was compared with that of state-of-the-art anodes for phenol electro-oxidation: antimony-doped tin oxide ( SnO 2 –Sb 5+ ) and ruthenium oxide ( RuO 2 ): first, under standard ambient conditions, and then, under the conditions of a Polymeric Electrolyte Membrane (PEM) electrolyzer ( i.e. 85 °C and 30 bar) and of mild Catalytic Wet Air Oxidation (CWAO, i.e. 150 °C and 30 bar). Both reaction time and current density were varied to investigate their effect in the performances of the system as well as on the reaction mechanism. Both MnOx electrodes reported enhanced conversion efficiencies, up to ∼75%, at the highest pressure and temperature, and at the lowest applied current density, which influenced the process by improving dissolution of the O2 evolved, the reaction kinetics and thermodynamics, and by minimizing irreversibilities, respectively. The here reported MnOx films achieved conversion and mineralization efficiencies comparable to Sb-SnO 2 (that is the more toxic) and RuO 2 (that is more expensive) materials, operating under mild CWAO operation conditions, which demonstrate the potential of the electrocatalytic HTHP process as a sustainable advanced oxidation technology for wastewater treatment or electrosynthesis applications. Graphical abstract: Highlights: Low-cost electrodeposited manganese oxides electro-oxidize refractory organics with high efficiencies. Mn2 O3 phase gives the best performance (up to 77%) under mild catalytic wet air oxidation conditions (150°C and 30 bar). MnOx-electrodes could allow process intensification of electro-oxidation under mild temperature and pressure conditions.